(untitled) (Indian Journal of Arid Horticulture, 2018)
Dry-land horticulture has immense and diverse potentialities in providing nutrition rich food and social security to inhabitants of desert and tribal area of the north-western India. While assessing distinctness studies of the hot arid and semi-arid agro-climate of Rajasthan state during 19941997 for horticultural perspective, it is concluded that un-availability of requisite cropgenotype and production techniques are two main constraints in promoting vegetable cultivation. Traditionally, kachri (Cucumis melo var. callosus / agrestis), kakadia / snap melon (Cucumis melo var. momordica), mateera (Citrullus lanatus), tinda (Praecitrullus fistulosus) and guar (Cyamopsis tetragonoloba) is grown with mixed cropping. Besides, khejri (Prosopis cineraria) is playing very important role in long-established farming system, and its tender pods are vegetable use. With the establishment of NRCAH during 1993 at Bikaner, systematic research work for conservation and utilization of native crop-plants germplasm having vegetable significance was started. The crop-genotypes studies over 45 vegetables from 19952005 at CIAH demonstrated that there is magnificent scope in obtaining higher marketable yields, provided better and trait-specific genotypes, and adopting khejri based production site management concept (HBCPSMA),. Thus, the varietal and technological advancement in arid vegetables is a boon towards better nutrition and farmer’s income under resource poor desert environment.